Production and Dissemination of Feminism in the Chilean Post-Dictatorship: The Cases of la Casa de la Mujer la Morada, la Editorial Cuarto Propio, the Revista de Crítica Cultural and Radio Tierra, 1990-2007; [Producción y Difusión del Feminismo en la Posdictadura Chilena: Los Casos de la Casa de la Mujer la Morada, la Editorial Cuarto Propio, la Revista de Crítica Cultural y la Radio Tierra, 1990-20071] - Moyano-Barahona, C (University of Coimbra, 2023)
This article analyzes the formation of the intellectual network in which feminist knowledge was produced, circulated and spread between 1990 and 2007, a period that covers almost two post-dictatorship decades in Chile. The main objective is to historicize the functioning of the network, its agents and the concepts that helped build the cognitive frameworks of contemporary feminism, as one of the forms of knowledge that was part of the "narratives of discomfort" and that strongly criticized the type of democracy and the processes of democratization after 1990, through a methodological intersection between political history and intellectual history. © 2023 Universidade de Coimbra - Faculdade de Letras. All rights reserved.